DDDR-39. IDENTIFICATION OF A NOVEL THERAPEUTIC TARGET THAT IS SYNTHETICALLY LETHAL WITH MUTANT IDH INHIBITOR IN GLIOMA USING THE CRISPR/CAS9 GENOME EDITING TECHNOLOGY. (14th November 2022) - Maeda, Sachi; Aoki, Kosuke; Hinohara, Kunihiko; Yamaguchi, Junya; Ohka, Fumiharu; Motomura, Kazuya; Kibe, Yuji; Natsume, Atsushi; Saito, Ryuta
Abstract: Diffuse glioma is the most frequent and malignant neuroepithelial tumor in the central nervous system. IDH mutations are the most frequent genetic mutations in adult gliomas. The WHO Classification of Tumors, 5th edition, volume 6: Central Nervous System Tumours revised in 2021, defines the presence of IDH mutations in gliomas as astrocytoma IDH-mutant and oligodendroglioma IDH-mutant and 1p/19q-codeleted. In addition, more than 90% of IDH mutations found in gliomas are IDH1 R132H mutation. Several clinical trials of mutant IDH1 inhibitors targeting the IDH1 R132H mutation have shown their efficacy, but it has also been reported that IDH1 inhibitors alone may not provide sufficient tumor suppression. In this study, we performed genome-wide knockout screening using CRISPR/Cas9 genome editing technology to search for new drug targets that are synergistic with the mutant IDH1 inhibitor DS-1001b. The results of CRISPR screening and RNA sequence analysis revealed that several metabolism-related genes are factors that define resistance to mutant IDH inhibitor. In a tumor suppression study, treatment of two IDH1 R132H mutant glioma cell lines (MGG152 and BT142) with mutant IDH1 inhibitor suppressed production of the oncometabolite D2-HG, but did not significantly alter cell growth. However, when mutant IDH1 inhibitor were combined with inhibitor for metabolism-related genes, cell survival was significantly reduced, and the effects were synergistic. In this study, we found that administration of mutant IDH inhibitors to IDH mutant gliomas significantly altered intratumor metabolism using various molecular approaches. We then identified targets that, when combined with mutant IDH inhibitor, provide synergistic tumor suppression. These results are expected to provide a new therapeutic approach for a subset of patients who have difficulty responding to mutant IDH1 inhibitors.